Combustion instability characteristics in a dump combustor using different hydrocarbon fuels. (May 2019) - Hwang, D.; Song, Y.; Ahn, K.
ABSTRACT: The combustion instability characteristics in a model dump combustor with an exhaust nozzle were experimentally investigated. The first objective was to understand the effects of operating conditions and geometric conditions on combustion instability. The second objective was to examine more generalised parameters that affect the onset of combustion instability. Three different premixed gases consisting of air and hydrocarbon fuels (C2 H4, C2 H6, C3 H8 ) were burnt in the dump combustor at various inlet velocity, equivalence ratio and combustion chamber length. Dynamic pressure transducer and photomultiplier tube with a bandpass filter were used to measure pressure fluctuation and CH* chemiluminescence data. Peak frequencies and their maximum power spectral densities of pressure fluctuations at same equivalence ratios showed different trends for each fuel. However, the dynamic combustion characteristics of pressure fluctuations displayed consistent results under similar characteristics chemistry times regardless of the used hydrocarbon fuels. The results showed that characteristic chemistry time and characteristic convection time influenced combustion instabilities. It was found that the convective-acoustic combustion instability could be prevented by increasing the characteristic chemistry time and characteristic convection time.